Novel benzamido derivatives as PTP1B inhibitors with anti-hyperglycemic and lipid-lowering efficacy - Yanbo Tang; Xiaolin Zhang; Zheng Chen; Wenwen Yin; Guanglei Nan; Jinying Tian; Fei Ye; Zhiyan Xiao (Elsevier, 2018)
Based on a non-competitive and selective PTP1B inhibitor reported by us previously, thirty-nine benzamido derivatives were designed and synthesized as novel PTP1B inhibitors. Among them, twelve compounds exhibited IC50 values at micromolar level against human recombinant PTP1B, and most of them exhibited significant selectivity to PTP1B over TC-PTP and CD45. Further evaluation of the most potent compound 27 on high-fat diet (HFD)-induced insulin-resistant (IR) obese mice indicated that 27 could modulate glucose metabolism and ameliorate dyslipidemia simultaneously. KEY WORDS: PTP1B inhibitors, Benzamido derivatives, Structureactivity relation-ship, Anti-hyperglycemic, Lipid-lowering